Measuring the Unmeasurable by IR Spectroscopy: Carbon Deposition Kinetics in Dry Reforming of Methane. Issue 15 (30th May 2018) - Ren, Jiazheng; Lee, Alex Chinghuan; Cheng, Kai; Li, Ming; Chen, Yongsheng
Abstract: Dry reforming of methane converts two greenhouse gases to syngas, and Ni catalysts are commonly used for this reaction. A major catalyst deactivation mechanism is carbon deposition. Although numerous kinetic modelling works have been performed on carbon formation, there have been only scarce attempts to measure carbon deposition kinetics under relevant (but not real) conditions, owing to technical difficulties. Here, we report the first successful measurements of the kinetics under real reaction conditions. This was made possible by using a novel algorithm that we have developed. We use IR to measure the molar fractions of unreacted CH4 and CO2, and reaction products, CO and H2 O, in the effluent from the reactor. By applying the general mass balance principle and the relevant reaction stoichiometries, the carbon deposition rate as well as the flow rates of all these gases in the effluent, including H2, are calculated. Compared to the dominant GC‐based approach for catalyst performance evaluation, this method has much higher time resolution and much smaller measurement errors. Abstract : Measuring the unmeasurable : Carbon deposition rates are measured for the first time under real reaction conditions in dry (CO2 ) reforming of methane. Although unmeasurable by IR directly, they are calculated as a function of the molar fractions of CO2, CH4, CO, and H2 O, which are measurable by IR spectroscopy. This was made possible by applying mass balance and the relevant reaction stoichiometries.